Integration of a peer practitioner in a hospital unit for patients with psychotic disorders: an exploratory qualitative study - Lequin, Pierre; Suter, Caroline; Mazallon, Roxane; Brodard, Rachèle; Abrahamyan Empson, Lilith; Robalo, Bruno; Conus, Philippe; Nguyen, Alexandra; Favrod, Jérôme (Frontiers in Psychiatry, 2023)
Studies on the integration of Peer Mental Health Practitioners (PMHP) in hospitals are sparse, despite significant benefits being reported for patients and professionals. The integration of PMHP requires the consideration of several parameters and a change in the culture of care. This study aims to understand the impact of the integration of a PMHP in a hospital unit caring for patients with psychiatric disorders. To this end, qualitative content analysis of three focus groups with the interdisciplinarity team were conducted. A consulting PMHP was integrated into the entire research process. Data analysis revealed five main themes: the importance of integration, benefits for patients linked to the identification process, benefits for the team and institution, potentials risks, and perspectives. The study was conducted in a hospital setting with patients suffering from severe psychiatric disorders associated with behavioral disturbances. The benefits reported in the results outline the feasibility of PMHP integration in an acute psychiatric care setting. Nevertheless, further formalization of the PMHP role is required to minimize possible areas of tension between respective fields of activity of each professional.